Shielding of the geomagnetic field reduces hydrogen peroxide production in human neuroblastoma cell and inhibits the activity of CuZn superoxide dismutase - Hai-tao Zhang; Zi-jian Zhang; Wei-chuan Mo; Ping-dong Hu; Hai-min Ding; Ying Liu; Qian Hua; Rong-qiao He (Protein & Cell, 2017)
Abstract Accumulative evidence has shown the adverse effects of a geomagnetic field shielded condition, so called a hypomagnetic field (HMF), on the metabolic processes and oxidative stress in animals and cells. However, the underlying mechanism remains unclear. In this study, we evaluate the role of HMF on the regulation of cellular reactive oxygen species (ROS) in human neuroblastoma SH-SY5Y cells. We found that HMF exposure led to ROS decrease, and that restoring the decrease by additional H2O2 rescued the HMF-enhanced cell proliferation. The measurements on ROS related indexes, including total anti-oxidant capacity, H2O2 and superoxide anion levels, and superoxide dismutase (SOD) activity and expression, indicated that the HMF reduced H2O2 production and inhibited the activity of CuZn-SOD. Moreover, the HMF accelerated the denaturation of CuZn-SOD as well as enhanced aggregation of CuZn-SOD protein, in vitro. Our findings indicate that CuZn-SOD is able to response to the HMF stress and suggest it a mediator of the HMF effect.